Development of the learning to learn competence in the university context: flipped classroom or traditional method? - María Espada; José Antonio Navia; Patricia Rocu; Maite Gómez-López (Association for Learning Technology, 2020)
This study analyses the use of a flipped classroom to develop the 'learning to learn' competence in the university context. This research was conducted on a subject about Applied Teaching Methodology included in the Physical Activity and Sports Science degree at the Polytechnic University of Madrid (Spain). A total of 110 university students (mean age 21.6 ± 3.0 years) participated in the research and were divided into two groups: one group (44 students) received an intervention based on the traditional method (with theoretical classes and resolved questions) and the other group (66 students) received an intervention using the flipped classroom method; self-perception of the level of development of the 'learning to learn' competence was analysed before and after the intervention. The design involved two groups that followed different types of teaching (traditional vs. flipped classroom) × two moments in time (before and after).This study did not find any significant differences between the traditional and flipped classroom method, in the perception of the development of the 'learning to learn' competence.